Analysis of bank capital and profitability for the top 1000 banks in the worlds - Gan, Yoke Wah (2011)
The purpose of this research is to analyse the relationship between capital and profitability for banks in the three regions, Asia, Europe and the United States for two years, 1992 and 1993, that are ranked among the Top 1000 banks in the world by The Banker. It takes the lead from Berger (1995) who found that capital-asset ratios have positive effects on profitability. Besides the direct impact of capital on profitability through lower interest expenses, this study recognises that capital has an indirect impact on profitability through its effects on the bank's volume of assets. The bank's volume of assets may increase when capital increase but the ultimate profitability of the bank depends largely on the composition and pricing of the assets which in turn depend on factors like competition, regulation, management's strategy and the general economic environment affecting the level of interest rates.